A Case Study Approach for Economic Valuation of Marine Ecosystem Services - Gopinath, Majendiran; Muthazhagu, M. (International Journal of Accounting and Economics Studies, 2025)
Coastal ecosystems are defined by interactions between the land and oceanic systems. All over the world, there exists diversity in coastal ecosystems, ecosystem services, and the related human activities in coastal regions. As a result, coastal regions are often characterized by higher population density, dependence on ecosystem services, population pressure, ecosystem degradation, and alteration. Coastal regions face the threats of extreme climatic events, changes in temperature and rainfall patterns, sea level rise, tidal water surge, cyclones, and coastal flooding, among several other processes. Additional sources of threats include coastal erosion and accretion, shoreline change, and anthropogenic threats. High degree of ecosystem dependence in coastal regions, alteration and degradation of coastal ecosystem services, and several human, social, economic, institutional, and other factors and their interactions result in vulnerability and welfare loss in the human and economic system. The study discusses applicable economic valuation techniques—including market-based methods, travel cost, and choice experiments—for assessing the full value of marine ecosystem services. It is evident from the findings that the role of the community in carrying out occupational practices differed across occupation categories. Based on their role in the community, the occupations under study could be divided into four categories. These include activities that are entirely individual, entirely group, entirely individual with organizational support, and entirely individual with community support.